The Effect of Interest in Physical Education Classes on Identification with School: The Mediating Role of Teacher Feedback - Yücekaya, Mehmet Akif (Bartin University, 2026)
This research aims to examine the influence exerted by secondary school students’ Interest in Physical Education Classes (IPEC) in shaping their level of identification with school, as well as the intermediary function of perceived teacher feedback within this association. The participant group for this research consisted of 493 students attending different middle schools in Adıyaman. The study was conducted within the framework of the correlational survey model of quantitative research methods; the influence of students’ IPEC in predicting school identification, as well as the intermediary contribution of teacher feedback within this association, was tested using structural equation modelling. The findings show that students’ IPEC emerged as a significant predictor of school identification, both directly (? = 0.2198, p < .001) and indirectly through teacher feedback (? = 0.0323, p = .002). Teacher feedback acts as a mediating factor in this relationship, linking students’ IPEC to their sense of school affiliation. In conclusion, the findings indicated that students’ IPEC, in conjunction with teacher feedback, plays a decisive role in their identification with school.
Keywords: Psychological Foundations of Education; Eğitimin Psikolojik Temelleri; Development of Physical Education and Education Programs; Beden Eğitimi ve Eğitim Programlarının Geliştirilmesi